THE EFFECTS OF DIGITAL TECHNOLOGY ON OPPORTUNITY RECOGNITION (Conferencea, 2022)
Recognizing opportunities enabled by digital technology has become a competitive necessity in today’s digital world. However, opportunity recognition is a major challenge given the influence of digital technology, which not only disperses agency across various actors, but also blurs boundaries between customers, companies, products, and industries.